CHARACTER PSYCHOLOGY AND INNER CONFLICT IN HENRY JAMES’S “THE BEAST IN THE JUNGLE” - Sadullayev Feruz Baxshillayevich; Savriyeva Farangiz Suxrob qizi (Innovate Conferences, 2025)
This thesis explores the psychological depth and inner conflict of John Marcher in Henry James’s “The Beast in the Jungle”, highlighting how Marcher’s downfall is rooted not in fate but in his own emotional passivity. Through the analysis of the novel reveals how this internal battle ultimately destroys his capacity for human connection.
Keywords: psychological depth, inner conflict, downfall, emotional passivity, internal battle, capacity, human connection.